The Ambiguity of Criminalizing Business Decisions: An Analysis of Legal Realism and the Business Judgment Rule in Supreme Court Decision Number 121 K/Pid.Sus/2020 - Afriansyah Tanjung; Muhammad Marizal; Irawan Malebra (Universitas Sriwijaya, 2026)
The phenomenon of criminalizing business decisions within State-Owned Enterprises (SOEs) shows that there is a serious tension between the logic of corporate governance and the goal of eradicating corruption. The Supreme Court Decision No. 121 K/Pid.Sus/2020 regarding the acquisition of BMG Australia by PT Pertamina (Persero) is an example of how managerial actions carried out through legitimate corporate procedures can be construed as criminal acts because they lead to state losses. This study aims to analyze the ambiguity of the criminalization of business risk through a doctrinal legal approach combined with the perspective of legal realism. The research method uses a conceptual analysis of the Business Judgment Rule as a standard of accountability of the board of directors in decision-making, as well as a case approach to the Supreme Court's legal considerations with qualitative analysis techniques based on juridical reasoning. The results of the study show that judges emphasize more on the results of decisions in the form of state losses as an indicator of error, so that the line between economic risk and unlawful acts becomes blurred. This condition poses a potential chilling effect that can hinder the courage of the board of directors in carrying out business strategies in risk-intensive SOEs. This research contributes to the need to reformulate the application of Business Judgment Rule in corporate corruption cases to prevent excessive criminalization of business decisions that are not based on malicious intent or conflict of interest.